Filling the Vacancy of Legislative Seats from a Political Party Dissolved by the Constitutional Court: Pengisian Kekosongan Kursi Anggota Legislatif dari Partai Politik yang Dibubarkan oleh Mahkamah Konstitusi - Nurmagulita, Okky Alifka (Universitas Islam Indonesia, 2023)
Political parties are an important component in Indonesia's democratic political system. Political parties are needed because they have a position and role as a strategic liaison between government processes and the citizens. The dissolution of political parties carried out by the Constitutional Court can have an impact on vacant legislative member seats. The formulation of the problem of this research is what is the mechanism for filling vacancies in legislative seats resulting from the dissolution of political parties by the Constitutional Court? This is a normative juridical with a statutory approach. The data collection technique used is through document and literature studies of secondary data in the form of primary, secondary and tertiary legal materials. The results of this research conclude that filling vacancies in legislative seats as a result of the dissolution of political parties by the Constitutional Court can be done using a plebiscite mechanism.Key words: legislative institution, constitutional court, and dissolution of political parties AbstrakPartai politik merupakan komponen penting dalam sistem politik Indonesia yang demokratis. Partai politik dibutuhkan karena memiliki posisi dan peran sebagai penghubung strategis antara proses pemerintahan dengan warga negara. Pembubaran partai politik yang dilakukan oleh Mahkamah Konstitusi dapat berdampak terhadap kekosongan kursi anggota legislatif. Rumusan masalah dari penelitian ini adalah bagaimana mekanisme pengisian kekosongan kursi anggota legislatif akibat pembubaran partai politik oleh Mahkamah Kontitusi? Jenis penelitian ini adalah yuridis normatif dengan pendekatan perundang-undangan. Teknik pengumpulan data yang digunakan yakni melalui studi dokumen dan literatur terhadap data-data sekunder berupa bahan-bahan hukum primer, sekunder, dan tersier. Hasil dari penelitian ini menyimpulkan bahwa pengisian kekosongan kursi legislatif sebagai akibat dari dibubarkannya partai politik oleh Mahkamah Konstitusi dapat dilakukan dengan mekanisme plebisit.Kata-kata kunci: lembaga legislatif, mahkamah konstitusi, dan pembubaran partai politik